2021
DOI: 10.3390/agriculture11060569
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Rice Yield in Malaysia: A Panel Data Analysis

Abstract: Climate change is a global problem since many countries worldwide are becoming increasingly vulnerable to natural disasters. Numerous climate models in various studies project a decline in agricultural productivity that will mainly be due to excessive heat in tropical and subtropical regions, especially in Southeast Asia. As a Southeast Asian country, Malaysia is no exception to this problem. Hence, the present study aimed to examine the impact of climate change on rice yields in Malaysia. A panel data approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 54 publications
(59 reference statements)
1
11
0
1
Order By: Relevance
“…Oh-e et al 134 concluded that any additional increase in mean T max above 28 °C could diminish rice yields, and this study noted T max (Table 4 ) to be 28.90 °C (> 28 °C), negatively influencing rice yield. The T min coefficient of regression was significantly positive (Table 5 ), indicating a significant increase in rice yield for every 1 °C increase in T min , supporting the findings of Zhang et al 114 , Guntukula 118 , and Tan et al 65 , but contradicting Zhang et al 135 and Ghadirnezhad and Fallah 136 . However, Cooper et al 137 found no change in rice yield with rising T min .…”
Section: Resultssupporting
confidence: 62%
“…Oh-e et al 134 concluded that any additional increase in mean T max above 28 °C could diminish rice yields, and this study noted T max (Table 4 ) to be 28.90 °C (> 28 °C), negatively influencing rice yield. The T min coefficient of regression was significantly positive (Table 5 ), indicating a significant increase in rice yield for every 1 °C increase in T min , supporting the findings of Zhang et al 114 , Guntukula 118 , and Tan et al 65 , but contradicting Zhang et al 135 and Ghadirnezhad and Fallah 136 . However, Cooper et al 137 found no change in rice yield with rising T min .…”
Section: Resultssupporting
confidence: 62%
“…Increased rainfall intensity was cited by nearly 90% of rice producers as a perceived climate change concern. It is undeniable that higher rainfall intensity has an impact on rice production, resulting in lower yields and inferior grains [53]. Increased rainfall intensity causes erosion, which can destroy rice fields and rice grains.…”
Section: Farmers' Perception Of Climate Eventsmentioning
confidence: 99%
“…For instance, the Fusarium head blight of wheat crops is caused by the Fusarium species and its chances of an attack were increased due to high humidity and hot environment (Shah et al, 2018 ). A similar study has shown a direct interaction between insect pests and diseases and higher temperature and carbon dioxide levels in rice production (Iannella et al, 2021 ; Tan et al, 2021 ; Tonnang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 83%